Selectivity and Reactivity of ZrIV and CeIV Substituted Keggin Type Polyoxometalates Toward Cytochrome c in Surfactant Solutions - Quanten, Thomas; De Mayaer, Tessa; Shestakova, Pavletta; Parac-Vogt, Tatjana N. (Frontiers in Chemistry, 2018)
In this paper we investigate the effect of three different types of surfactants, on the hydrolysis of Cytochrome c (Cyt c), a predominantly α helical protein containing a heme group, promoted by [Ce(α PW11O39)2]10- (CeK) and [Zr(α PW11O39)2]10- (ZrK) polyoxometalates. In the presence of SDS, Zw3 12, or CHAPS surfactants, which are commonly used for solubilizing hydrophobic proteins, the specificity of CeK or ZrK toward hydrolysis of Cyt c does not change. However, the hydrolysis rate of Cyt c by CeK was increased in the presence of SDS, but decreased in the presence of CHAPS, and was nearly inhibited in the presence of Zw3 12. The Circular dichroism and Tryptophan fluorescence spectroscopy have shown that the structural changes in Cyt c caused by surfactants are similar to those caused by POMs, hence the same specificity in the absence or presence of surfactants was observed. The results also indicate that for Cyt c hydrolysis to occur, large unfolding of the protein is needed in order to accommodate the POMs. While SDS readily unfolds Cyt c, the protein remains largely folded in the presence of CHAPS and Zw3 12. Addition of POMs to Cyt c solutions in CHAPS results in unfolding of the structure allowing the interaction with POMs to occur and results in protein hydrolysis. Zw3 12, however, locks Cyt c in a conformation that resists unfolding upon addition of POM, and therefore results in nearly complete inhibition of protein hydrolysis.